2018
DOI: 10.12968/johv.2018.6.8.404
|View full text |Cite
|
Sign up to set email alerts
|

What makes health visiting successful—or not? 2. The service journey

Abstract: This is the second of two papers reporting evidence from a programme of research that focused on how health visiting works, including service user and workforce perspectives. Evidence and professional expertise indicate that a set of essential features enable health visitors to achieve the desired impact of improving child public health. These include organising services in a way that enables positive parent/health visitor relationships, continuity and coordination and the flexibility to use professional knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, the quantitative data showed almost 75% of the HVs in both areas perceived a lack of contacts in the home was a major barrier to identifying women's PNMH problems. Interview data suggested that HVs felt home contacts facilitated the building of relationships, and that the home environment was perceived to engender feelings of security and confidence for women thereby facilitating disclosure of pre-existing/current PNMH problems, these findings are reinforced in the literature (34). Home visits were also perceived to be beneficial to HVs as they fostered a holistic approach to their assessment of women, enabling HVs to observe women and assess how they were coping and/or observe women's parenting.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, the quantitative data showed almost 75% of the HVs in both areas perceived a lack of contacts in the home was a major barrier to identifying women's PNMH problems. Interview data suggested that HVs felt home contacts facilitated the building of relationships, and that the home environment was perceived to engender feelings of security and confidence for women thereby facilitating disclosure of pre-existing/current PNMH problems, these findings are reinforced in the literature (34). Home visits were also perceived to be beneficial to HVs as they fostered a holistic approach to their assessment of women, enabling HVs to observe women and assess how they were coping and/or observe women's parenting.…”
Section: Discussionmentioning
confidence: 83%
“…Analysis of serious case reviews found that thresholds for CSC intervention may be high because of pressures on the system and heavy workloads (Social Care Institute for Excellence, 2016b). If thresholds are not met, an HV may become the sole worker involved with high‐risk families, which can cause anxiety and concern both for the families who are not receiving adequate social care, and other families for whom the HV is responsible, who may be receiving less support as a result (Cowley et al, 2013). Possible solutions include the introduction of ‘threshold moderation meetings’, double screening of referrals, feedback on referrals, training and support for professionals making referrals and encouraging professionals to challenge decisions and escalate concerns where necessary (Social Care Institute for Excellence, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…As health visitor academics and researchers, we were aware from anecdotal evidence of differences in caseload and team organisation. This includes health visitors working within integrated teams with early years providers and with various caseload models, reflecting the team/caseload arrangements described by Cowley et al (2018). What is more, this appears to be a rapidly changing picture.…”
Section: Methodsmentioning
confidence: 99%